Development of an Experimentally Validated MCNP6 Model for 11C Production via the 14N(p, α) Reaction Using a GE PETtrace Cyclotron. (2nd July 2020) - Hall, Amy; Gum, Daniel A.; Ferrieri, Richard; Brockman, John; Bevins, James E.
Abstract: The General Electric (GE®) PETtrace 860 cyclotron at the Missouri University Research Reactor (MURR) facility is used extensively for medical and research radioisotope production. However, no model exists of its performance, and the proton beam's energy and spatial distribution are unmeasured. Here, an MCNP6 model was developed to improve upon the performance of the cyclotron target systems that are routinely utilized for research and medical radioisotope production. Since the cyclotron beam energy and profile have a significant impact on the efficiency and character of radioisotope production, the MURR cyclotron proton beam energy was measured using high-purity copper stacked foil activation to be 14.6 ± 0.2 MeV, a significant reduction from the stated 16.4 MeV. Phosphor plate imaging was also used to radiographically image the distribution of radioisotope production within the copper foils and characterize the beam spatial and intensity profile. Total target activity was quantified by trapping the 11 C on a solid adsorbent and measuring the amount in an ion chamber. Effective target densities were calculated for irradiations conducted with beam currents between 5 and 40 μA. The measured beam and target characteristics were used to develop an MCNP6 model of 11 C production. Through use of the model, it was determined that the targets were, at most, 41% efficient as a thick target design resulting in up to 11.80-MeV average protons impinging on the target walls leading to potential contamination from hot ion recoils.